2021
DOI: 10.1017/jfm.2021.1018
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of aerofoil tonal noise at low Mach number

Abstract: This paper presents an experimental investigation of aerofoil tones emitted by a controlled-diffusion aerofoil at low Mach number ( $0.05$ ), moderate Reynolds number based on the chord length ( $1.4 \times 10^{5}$ ) and moderate incidence ( $5^{\circ }$ angle of attack). Wall-pressure measurements have been performed along the suction side of the aerofoil to reveal the acoustic source mechanisms. In particular, a feedback loop is f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 67 publications
2
11
0
Order By: Relevance
“…3(a) and (b), respectively, a spanwise coherent structure or small-scale turbulent eddies. The coherent structures observed in the present study are similar to those previously reported in both numerical simulations and experiments [12,27].…”
Section: A Flow Dynamicssupporting
confidence: 92%
See 1 more Smart Citation
“…3(a) and (b), respectively, a spanwise coherent structure or small-scale turbulent eddies. The coherent structures observed in the present study are similar to those previously reported in both numerical simulations and experiments [12,27].…”
Section: A Flow Dynamicssupporting
confidence: 92%
“…When combined, these parameters will dictate the physical mechanisms responsible for airfoil tonal noise generation including the detachment and reattachment dynamics of separation bubbles, and the subsequent shedding of coherent structures. For instance, it has been reported that vortex merging [10,22], bursting [12,[23][24][25][26][27], and intermittency [6,10,12,20] take place downstream of suction side separation bubbles. Thus, it is clear that the investigation of the flow dynamics driven by the separation bubbles is important to understand the noise sources.…”
Section: Introductionmentioning
confidence: 99%
“…Considering flows with low to moderate Reynolds numbers, conducted an extensive experimental analysis of a NACA 0012 airfoil at a low angle of attack to identify the relation between the tonal noise and the flow structures. The study characterized coherent structures that are convected and scattered at the trailing edge, and concluded that they play a main role in the tonal noise and reinforcing the significance of such a phenomenon in the airfoil self-noise (Arcondoulis et al 2010;Abreu, Cavalieri & Wolf 2017;Sanjose et al 2019;Sano et al 2019;Jaiswal et al 2022;). In addition, when considering the Reynolds number and angle of attack, they show that the problem can be separated between pressure-side and suction-side regimes in the tonal noise generation, based on the eventual suppression of tones if boundary layer transition is forced on one of the airfoil sides.…”
Section: Introductionmentioning
confidence: 85%
“…It is clear that tonal noise is related to a boundary or shear layer that is transitional (Pröbsting, Scarano & Morris 2015), and several studies analyse the problem from different perspectives taking into account the relationship with the Reynolds and Mach numbers and the angle of attack. The current view is that tonal noise is the result of a feedback mechanism, with coherent structures that grow on a separated shear layer and are scattered as an acoustic wave at the trailing edge, which excites new disturbances in an upstream location, thus closing the loop (Fosas de Pando, Schmid & Sipp 2014; Sanjose et al 2019;Jaiswal et al 2022;Ricciardi, Wolf & Taira 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In fluid dynamics and turbulence analyses, POD is used to replace the Navier-Stokes equations (Berkooz et al 1993). Jaiswal et al (2022) used POD to explain airfoil tonal noise amplitude reduction. Kim et al (2022) studied the influence of varying the frequency of a synthetic jet on flow separation over an airfoil using POD.…”
Section: Introductionmentioning
confidence: 99%